Photosynthetic decline in aging perennial grass is not fully explained by leaf nitrogen. (4th October 2022) - Tejera, Mauricio; Boersma, Nicholas N; Archontoulis, Sotirios V; Miguez, Fernando E; VanLoocke, Andy; Heaton, Emily A
Abstract: Aging in perennial plants is traditionally observed in terms of changes in end-of-season biomass; however, the driving phenological and physiological changes are poorly understood. We found that 3-year-old (mature) stands of the perennial grass Miscanthus×giganteus had 19–30% lower A net than 1-year-old M.×giganteus (juvenile) stands; 10–34% lower maximum carboxylation rates of Rubisco and 34% lower light-saturated A net ( A sat ). These changes could be related to nitrogen (N) limitations, as mature plants were larger and had 14–34% lower leaf N on an area basis (Na ) than juveniles. However, N fertilization restored Na to juvenile levels but compensated only 50% of the observed decline in leaf photosynthesis with age. Comparison of leaf photosynthesis per unit of leaf N (PNUE) showed that mature stands had at least 26% lower PNUE than juvenile stands across all N fertilization rates, suggesting that other factors, besides N, may be limiting photosynthesis in mature stands. We hypothesize that sink limitations in mature stands could be causing feedback inhibition of photosynthesis which is associated with the age-related decline in photosynthesis. Abstract : Leaf nitrogen content did not fully explain a 10–34% decrease in leaf photosynthesis in aging Miscanthus×giganteus . Our data imply that lack of strong carbohydrate sinks late in the season may drive leaf-level photosynthetic decline.